2021
DOI: 10.3390/pharmaceutics13122085
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Third-Generation Tetracycline Antibiotics and New Perspectives

Abstract: The tetracycline antibiotic class has acquired new valuable members due to the optimisation of the chemical structure. The first modern tetracycline introduced into therapy was tigecycline, followed by omadacycline, eravacycline, and sarecycline (the third generation). Structural and physicochemical key elements which led to the discovery of modern tetracyclines are approached. Thus, several chemical subgroups are distinguished, such as glycylcyclines, aminomethylcyclines, and fluorocyclines, which have excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 164 publications
(300 reference statements)
1
39
0
Order By: Relevance
“…Several in vitro and mouse model studies showed sarecycline preferentially works against clinically relevant Gram-positive bacteria over Gram-negative bacteria [ 29 , 30 , 31 ]. This narrow-spectrum activity is the consequence of a focused design effort to make sarecycline more selective for the Gram-positive bacterium C. acnes [ 32 ], providing dermatologists a means to improve antibiotic stewardship in acne vulgaris therapy. Against 55 clinical isolates of C. acnes , sarecycline had a minimum inhibitory concentration (MIC) ranging from 0.5 to 16 µg/mL [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and mouse model studies showed sarecycline preferentially works against clinically relevant Gram-positive bacteria over Gram-negative bacteria [ 29 , 30 , 31 ]. This narrow-spectrum activity is the consequence of a focused design effort to make sarecycline more selective for the Gram-positive bacterium C. acnes [ 32 ], providing dermatologists a means to improve antibiotic stewardship in acne vulgaris therapy. Against 55 clinical isolates of C. acnes , sarecycline had a minimum inhibitory concentration (MIC) ranging from 0.5 to 16 µg/mL [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…CaP-based bone-targeting therapies, including tetracycline, hydroxyapatite and bisphosphonates, have a high affinity for skeletal tissues and increase the topical concentration ( Figure 4 ). Tetracycline (TC) and its derivatives are an important class of broad-spectrum antibiotics ( Shi et al, 2020 ; Rusu and Buta, 2021 ). The tetracyclic naphthacene carboxamide ring is a basic structure.…”
Section: Cap-based Bone-targeting Therapeutic Strategy Can Be Designe...mentioning
confidence: 99%
“…Tetracyclines (Tc) represent a group of antibiotics with a broad spectrum of activities [ 1 , 2 ]. The first antibiotics from the class of tetracyclines (chlorotetracycline and oxytetracycline) were discovered at the end of 1940 s, with ultimately over 20 tetracyclines in use today [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first antibiotics from the class of tetracyclines (chlorotetracycline and oxytetracycline) were discovered at the end of 1940 s, with ultimately over 20 tetracyclines in use today [ 3 ]. They can be divided into three categories: I generation tetracyclines (chlorotetracycline, oxytetracycline, tetracycline, demeclocycline), II generation tetracyclines (doxycycline, minocycline, lymecycline, meclocycline, metacycline, rolitetracycline), and III generation ones (tigecycline, omadacycline, sarecycline) [ 2 , 4 ]. The I generation antibiotics are naturally synthesized, whereas the II and III generation ones are semi-synthetic.…”
Section: Introductionmentioning
confidence: 99%